EXERCISE FOR PATIENTS WITH ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION (STEMI) - Lale Wisnu Andrayani (Jurnal Kesehatan Prima, 2016)
Abstract : Heart disease is the highest cause of death and disability in the world. The disease is reported as the leading cause of death in The United States (Overbaugh ,2009). The data of basic health research in 2007 reported of Coronary Heart Disease (CHD) was the leading cause of death in Indonesia. Several studies reported the decreased of the heart disease, including coronary heart disease, myocardial repeated and the mortalitas heart disease by reducing risk factors, for instance, physical exercise. However, myocardial infarction occured after physical activity and intervention bedrest when initial handling could cause perception that physical exercise should be avoided after myocardial infarction attack. It leads to the need for adequate and appropriate information to minimize the patients’ misunderstanding in starting physical activity after the attack of STEMI in an attept to recover their heart function. Methods: the identification of relevant literature about physical exercise for STEMI on articles and research. Results: among 4 articles which had been reviewed were researches with randomized controlled trial (RCT) design. In general, the four researches found that physical exercise can provide significant profit either directly, to return heart function or indirectly, the reduction of risk factors. However, there was one (1) survey that explained that there was a risk of injury in physical exercise for STEMI patients, but it can be minimalized with knowledge and the appropriate procedure of exercise. Conclusion: in  early physical exercise for the patient with STEMI provides a positive impact which prosper for  heart function improvements, either through self repair mechanisms or through the reduction of risk factors. Therefore, the nurse needs to actively involved in the physical exercise program by providing information and facilitate the rehabilitation of the program.